KETERLIBATAN MASYARAKAT DALAM PENGEMBANGAN USAHA PARIWISATA DI WANA WISATA KAWAH PUTIH (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2015)
This study aims to determine the community's involvement in the development of tourism business at Wana Wisata Kawah Putih, Kaupaten Bandung. The method used is descriptive-qualitative by using the Nominal Group Technique (NGT) as a guide to analyze. Data were obtained from observations and interviews with informants purposively. The conclusion that the community is involved in functional or collaboration level.